A retórica da alteridade na “Relação da missão da serra da Ibiapaba”, do Padre Antônio Vieira - Santos, Fernanda Cristina da Encarnação dos (2018)
Antônio Vieira documents his travels, in the seventeenth century, through letters (epistolography) and various narratives. Among these texts is "Relação da missão da serra da Ibiapaba", produced in 1660th. In an attempt not only to write, but also to represent and legitimize his writing and his action, Vieira finds, in his discursive practice of travel, a multiplicity and a comprehensiveness of circumstances and places of writing, with several recipients. Thus, it is sought to analyze, in a rhetorical perspective, the "Relação da missão da serra da Ibiapaba", a narrative based on the rhetorical preceptives of Instituição Oratória, from Quintilian, and Do orador, from Cicero, fundamental works for the ignatian Order. The study of François Hartog (1999), in which the rhetorical categories from Herodotus's work, such as "comparison", "translation", "nomination", "classification", “inversion” and “converting”. These categories make possible the analysis of the rhetoric of alterity in the text "Relação", since they allow the Vieira’s narrator to describe and classify the indigenous tabajaras of the Ibiapaba mountain range. The thesis observes a narrative that is a solid component of several other writings about natives, produced by Antônio Vieira between 1650 and 1660th , in which the rhetoric-argumentative preceptives are maintained, in defense of a greater cause: the evangelization of the native tabajaras and the presence of the Jesuits in the Ibiapaba mountain range. The rhetorical analysis also allows us to conclude that the tabajaras actively negotiate with the Jesuits, and the considerations about them are not limited to characteristics such as "ignorance", "primitivism", "savagery", understanding them as an integral part of a complex process of colonization, based on the theoretical principles of the FifthEmpire.